Comparative Numerical and Experimental Study of Golden Angle and Conventional Agitator Impellers - Karki, Prayush Jung; Subedi, Abishek; Gaihre, Anupama; Chaulagain, Bikalpa; Shrestha, Strena; Chitrakar, Sailesh (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Conventional agitator impellers are found to be implemented in mixing tanks of various industries. The performance of these impellers is measured by the quality of the mixture and the cost of mixing in terms of the required power and time. This paper studies the possibility of replacing the conventional impellers with golden angle impellers for a better performance. The golden angle creates a natural spiral shaped impeller, which is an energy-efficient alternative for mixing tanks due to its natural tendency of minimizing the energy. A golden angle impeller has been designed in this study from CAD modelling and computed through CFD. The average velocity, torque, and power number are determined using numerical simulations from Solidworks 2020. The FloXpress solver is used to compute CFD and results from the golden angle impeller are compared with the same diameter of conventional agitator impeller. The results of CFD showed increase in the power output and the average velocity of the flow in the golden angle impeller to be 12.4% and 66.36% more than that of the marine impeller respectively. Moreover, the results from the simulation are validated through experiments by testing conductivity after mixing fine particles of blue vitriol in water, using 3D printed models of the impellers. The experimental study showed an average increase of the conductivity of the mixture and power consumption to be 5.39% and 17.6% more for the case of golden angle impeller respectively which was due to higher turbulence in golden angle impeller than marine impeller. After comparing the performance of the two impellers, it is found that the mixing process can be optimized significantly by using the golden angle impeller. By the given study it is concluded that the golden angle impeller is more preferrable where mixing process plays a significant role like during the production of pharmaceuticals, cosmetics, waste water management, dairy where manufacturing takes a very long time or when the rotational speed is quite low. The paper is aimed to determine the factors that yield the better performance, energy conservative and efficiency of the crafted golden angle impeller model with respect to widely commercialized impellers (marine impeller), addressing the prospects of minimizing the energy required.